Prevalence of depression and anxiety symptoms among female football players and non-players - Puš, Katarina; Kajtna, Tanja (Annales Kinesiologiae, 2022)
Purpose: Depression and anxiety are mental illnesses which affect many people worldwide. The purpose of this study is to determine the prevalence of depression and anxiety symptoms among Slovenian female football players and non-players. Methods: The sample consisted of Slovenian female football players playing in the Slovenian 1st female football league or youth league (n = 78) and non-player peers (n = 120) with an average age of the total sample 22±4 years. The participants filled out a questionnaire including some general questions (age, physical activity levels, participation in competitive sports), Beck Depression Inventory (BDI-II), Beck Anxiety Inventory (BAI), and Depression, Anxiety and Stress Scale (DASS-21). Results: The most commonly observed were normal and mild levels of depression and anxiety. According to the results of depression in BDI-II, 43.6% of athletes experienced moderate to severe depression compared to 15.8% of peers (p = 0.001). Results from DASS-21 show that 71.8% of athletes experience normal to mild symptoms of depression and 56.4% experience the same levels of anxiety. Similarly, 75% of peers experience normal to mild depressive symptoms and 56.7% reported normal to mild symptoms of anxiety. No statistical differences were found in these categories. Conclusion: We have gained insight into the current prevalence of depression and anxiety among female football players and their peers but more research needs to be done.